Real-time gross settlement and the costs of immediacy - Charles M. Kahn; William Roberds (Federal Reserve Bank of Atlanta, 1999)
Using a neoclassical monetary model, we investigate the welfare cost of a payment system that operates as a real-time gross settlement (RTGS) system. We illustrate how the cost of such systems does not ultimately derive from factors such as "payments gridlock" but instead from the credit constraints imposed by RTGS. We also investigate the welfare consequences of various approaches to the allocation of daylight credit by central banks. The two most popular approaches, collateralization and charging an administered intraday interest rate, are shown to be effective along some dimensions but flawed in others.
Keywords: 330; Money; Payment systems